2004
DOI: 10.1086/502369
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Nosocomial Pathogens on Hands After Contact With Environmental Surfaces Near Hospitalized Patients

Abstract: We examined the frequency of acquisition of bacterial pathogens on investigators' hands after contacting environmental surfaces near hospitalized patients. Hand imprint cultures were positive for one or more pathogens after contacting surfaces near 34 (53%) of 64 study patients, with Staphylococcus aureus and vancomycin-resistant Enterococcus being the most common isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
259
1
22

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(284 citation statements)
references
References 11 publications
2
259
1
22
Order By: Relevance
“…4,7,8 Several studies have indicated the importance of hand-touch sites as likely sources of HAI transmission via hands, and there may well be benefits from targeted cleaning of these sites. 1,9 The decontamination of clinical equipment is a nursing responsibility 8 but nurses' main priority is patient care, which may supersede cleaning duties when they are busy. 4 It is plausible that a sudden increase in workload leads to increased microbial levels in the environment and increased risk of infection for patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,8 Several studies have indicated the importance of hand-touch sites as likely sources of HAI transmission via hands, and there may well be benefits from targeted cleaning of these sites. 1,9 The decontamination of clinical equipment is a nursing responsibility 8 but nurses' main priority is patient care, which may supersede cleaning duties when they are busy. 4 It is plausible that a sudden increase in workload leads to increased microbial levels in the environment and increased risk of infection for patients.…”
Section: Discussionmentioning
confidence: 99%
“…After contact with the patient environment. 150,206,215,216 5. Perform hand hygiene with antimicrobial or nonantimicrobial soap when hands are visibly soiled (quality of evidence: n) .…”
Section: S E C T I O N 4 : R E C O M M E N D E D H a N D H Y G I E N mentioning
confidence: 99%
“…Microbiological contamination of the clinical environment is increasingly being highlighted as a source of infection, with direct contact with contaminated surfaces, indirect contact with contaminated surfaces via the hands of medical staff or equipment, and the air, all being recognised as potential sources of cross-infection [1][2][3]. High standards of cleaning and disinfection will contribute to minimising the risk of infection, and have been shown to play an important role in controlling outbreaks of infection [4,5].…”
Section: The Importance Of Environmental Decontaminationmentioning
confidence: 99%
“…The hospital environment can quickly become contaminated and act as a reservoir for infection, and evidence shows that significant contamination of nurse"s hands can occur from contact with environmental surfaces in the patient"s environment [2,[6][7][8]. Frequently-touched sites, such as door handles, light switches, bed tables and bed rails, are thought to provide the greatest potential risk for cross-infection [9].…”
Section: The Importance Of Environmental Decontaminationmentioning
confidence: 99%